2016
DOI: 10.1002/etc.3425
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the enhancement of toxicity caused by the coincubation of zinc oxide and copper nanoparticles in a fish hepatoma cell line

Abstract: Ecosystems are exposed to a wide variety of individual substances, including at the nano-scale; and the potential adverse effects of their interactions are an increasing concern. The purpose of the present study was to determine whether zinc oxide nanoparticles (ZnONPs) at a no-observed-effect concentration modulate the cytotoxicity of copper nanoparticles (CuNPs) in the fish hepatoma cell line PLHC-1 after 48 h of exposure and the contribution of the released ions to these effects. Cells were exposed to 50-nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Indeed, comparative studies suggested that Ag NPs were relatively less cytotoxic compared with ZnO NPs at the same mass concentrations (Elje et al, 2020; L. Jiang, Li, Xie, Liu, & Cao, 2019; Lee & Park, 2019; Wan et al, 2018), and therefore, adding Ag into ZnO nanocomplexes is expected to reduce the overall toxicity. This is also consistent with previous studies that showed that the presence of metal‐based NPs or metal ions alleviated the toxicity of other NPs (Hackenberg et al, 2017; Hernández‐Moreno et al, 2016; Hu, Hu, Li, & Zhao, 2016; Sun et al, 2020). However, we noticed that compared with soft materials such as liposomes (L. Shi, Wang, et al, 2020), polymers (Li et al, 2021; Zhou et al, 2020), chitosan (W. Han et al, 2019), lipids (Wan et al, 2018; Xie, Wan, Chen, Han, & Wang, 2020), soluble supramolecular NPs (X. Chen, Hu, et al, 2020), and proteins (An et al, 2020), the cytotoxicity of Ag–ZnO nanocomplexes was still relatively high.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, comparative studies suggested that Ag NPs were relatively less cytotoxic compared with ZnO NPs at the same mass concentrations (Elje et al, 2020; L. Jiang, Li, Xie, Liu, & Cao, 2019; Lee & Park, 2019; Wan et al, 2018), and therefore, adding Ag into ZnO nanocomplexes is expected to reduce the overall toxicity. This is also consistent with previous studies that showed that the presence of metal‐based NPs or metal ions alleviated the toxicity of other NPs (Hackenberg et al, 2017; Hernández‐Moreno et al, 2016; Hu, Hu, Li, & Zhao, 2016; Sun et al, 2020). However, we noticed that compared with soft materials such as liposomes (L. Shi, Wang, et al, 2020), polymers (Li et al, 2021; Zhou et al, 2020), chitosan (W. Han et al, 2019), lipids (Wan et al, 2018; Xie, Wan, Chen, Han, & Wang, 2020), soluble supramolecular NPs (X. Chen, Hu, et al, 2020), and proteins (An et al, 2020), the cytotoxicity of Ag–ZnO nanocomplexes was still relatively high.…”
Section: Discussionsupporting
confidence: 92%
“…The element Ti is more resistant to oxidation than Ce. In fish hepatoma cells, the effects of nZnO and nCuO mixture was enhanced and did not involve the mobilization of zinc ions [ 46 ]. The toxicity of nCuO was reduced when Zn 2+ was added to the incubation media leading to an increase in labile Zn in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Copper nanoparticles (CuNPs) have received much interest due to their unique physicochemical properties and low fabrication cost [6] . CuNPs are extensively used in electronics and metallic inks due to their optical, electrical, catalytic, and antimicrobial properties [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%